ANALISIS PENGGUNAAN APLIKASI WORDWALL PADA PEMBELAJARAN IPA KELAS IV DI SDN CIRACAS 05 PAGI - Nur Aidah; Nurafni Nurafni (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
The research objective to be achieved in this writing is to improve the learning outcomes of class IV (Four) students at SDN Ciracas 05 Pagi by using the wordwall application in science subjects. This type of research uses descriptive qualitative research methods. Qualitative descriptions are activities carried out to obtain data that are what they are in accordance with the facts that occur in the field. The stages of data collection are observation and interviews. Sources of data in this study using primary data sources and secondary data. Data analysis techniques are data collection, data reduction, data presentation and conclusion drawing. The results of the research on wordwall learning media is one of the interactive media that is easy to use, and can increase student interest and motivation in learning science class IV at SDN Ciracas 05 Pagi. Wordwall learning media can be used as one of the media used in bold learning as it is today. In addition to being easy and inexpensive to use, this media also has many alternative choices in presenting material and questions. So that educators can use other alternative options as other variations in packaging other subject matter. Fun and varied media will make students more active and more interested in following the learning process boldly.